Metformin Associated Lactic Acidosis in Clinical Practice – A Case Series - Schädle, Philipp; Tschritter, Otto; Kellerer, Monika (Experimental and Clinical Endocrinology & Diabetes, 2020)
Aims The aim of this case report is to specify the frequency and mortality of Metformin-Associated Lactic Acidosis (MALA) in emergency medicine, as the diagnosis seems to occur more often than estimated.Methods To identify the subjects, we developed screening criteria for MALA. We measured the serum metformin concentration to confirm the diagnosis in all patients fulfilling these criteria. Retrospectively the patients were grouped according to individual risk (according to a defined risk score) and the application of renal replacement therapy.Results From 2013 until 2018 we were able to identify 11 MALA patients revealing a frequency of 1:4,000 emergency patients. Six patients survived and five died in the follow-up. All three patients in the high-risk group died although all of them received renal replacement therapy. In the low-risk group (three patients, one with renal replacement therapy), all patients survived, while in the intermediate-risk group (five patients, one with renal replacement therapy) three patients survived and two died. Additional severe comorbidities also contributed to mortality.Conclusions Every patient matching the screening criteria of acute renal failure, lactic acidosis and continued intake of metformin can be considered a potential MALA case. A risk score assessment which includes severe comorbidities may help to identify high-risk individuals and should be evaluated in larger studies.To prevent MALA, patients should be trained to immediately interrupt their own metformin use when showing signs of volume depletion. Physicians should be aware of the additional risk factors such as co-medication with diuretics, ACE (angiotensin converting enzyme) ACE inhibitors and NSAIDs (non steroidal anti inflammatory drugs).
Keywords: metformin; lactic acidosis; renal insufficiency; type 2 diabetes mellitus